A Shield for the Tip of the Spear. (June 2021) - White, Samuel
The defence of superior orders is not new. However, within Australia, its statutory codification is lamentably underexplored. The 2018 Amendments to Part IIIAAA of the Defence Act 1903 (Cth) provides a neat catalyst to expand the defence and look at possible manners in which it can be constructed. Utilising a theoretical case study of Australian Defence Force members killing a possible terrorist, 'this article addresses' the key elements of the defence—what an order is, when can it be constructed as being manifestly unlawful and what does reasonable and necessary force mean for Australian Defence Force members.